The Issue of Entrusting of e-Deliveries to the Public Postal Service Operator in an EU Member State Illustrated by the Example of Poland - Jacek BUKO (Communications of International Proceedings, 2021)
Registered delivery service is used in all administrative, judicial and civil processes. In countries that are characterized by advanced development of the information society, physical registered delivery is currently being complemented or replaced by e-delivery. In several EU member states, rendering of these services has been entrusted on a long-term basis to the public postal service operator. Despite a number of social and economic benefits of this solution, it may be potentially contradictory to the Regulation (EU) on electronic identification and trust services for electronic transactions in the internal market (eIDAS), which provides for free trade in e-delivery services on the internal market. Analysis of statutory entrusting of e-delivery in Poland to the public postal service operator has confirmed the existence of such conflict, despite the fact that the service has been given the status of a service of general interest.
Keywords: E-Government; E-Administration; Cybercrime; E-Deliveries; Public Postal Service Operator.